Comparison of the acute outcome of two cryoballoon technologies for pulmonary vein isolation: An updated systematic review and meta-analysis. (October 2022) - Assaf, Amira; Bhagwandien, Rohit E.; Szili-Torok, Tamas; Yap, Sing-Chien
Abstract: Initial experience suggests that the POLARx cryoballoon system (Boston Scientific) has a similar procedural efficacy and safety as Arctic Front Advance Pro (AFA-Pro, Medtronic). We performed an updated systematic review and meta-analysis comparing POLARx and AFA-Pro. Embase, MEDLINE, Web of Science, Cochrane, and Google Scholar databases were searched until 12/01/2022 for studies comparing POLARx versus AFA-Pro in patients undergoing pulmonary vein (PV) isolation for AF. A total of 8 studies, involving 1146 patients from 11 European centers were included (POLARx n = 317; AFA-Pro n = 819). There were no differences in acute PV isolation, procedure time, fluoroscopy time, ablation time, minimal esophageal temperature, and risk of phrenic nerve palsy or thromboembolic events. Balloon nadir temperatures were lower for POLARx in all PVs. Compared with AFA-Pro, POLARx had a higher rate of first freeze isolation in the left inferior PV (LIPV) (odds ratio [OR]: 2.60; 95 % confidence interval [CI]: 1.06 to 6.43; P = 0.04), higher likelihood of time-to-isolation (TTI) recording in LIPV (OR: 2.91; 95 % CI: 1.54 to 5.49; P = 0.001) and right inferior PV (OR: 3.23; 95 % CI: 1.35 to 7.74; P = 0.008). In contrast, the TTI in LIPV was longer with POLARx in comparison to AFA-Pro (mean difference: 7.61 sec ; 95 % CI 2.43 to 12.8 sec ; P = 0.004). In conclusion, POLARx and AFA-Pro have a similar acute outcome. Interestingly, there was a higher rate of TTI recording in the inferior PVs with POLARx. This updated meta -analysis provides new safety data on esophageal temperature and thromboembolic events.